Information Quality and SMEs Innovative Performance: The Role of Knowledge Sharing and Business Process Management - amir fazel; behnam karamshahi; azin harandi (Iranian Journal of Information Processing & Management)
In the current business environment and the post-corona era, quality information builds the foundation of knowledge sharing, and facilitates business process management, and all of these play a fundamental role in the innovative performance of small and medium enterprises(SMEs). Therefore, the purpose of this research is to investigate the effect of information quality on the innovative performance of SMEs with regard to the mediating role of knowledge sharing and business process management.The research method is applied in terms of the goal and descriptive-survey in terms of the method. The statistical population of the research is 460 SMEs in Kerman, of which 210 companies were selected as a statistical sample based on Morgan's table. The sampling method is random sampling, and the research tool is a questionnaire whose validity and reliability were confirmed. Finally, 420 questionnaires were distributed among managers and vice presidents of companies.The data was analyzed with SPSS 26 and SmartPLS 3 software. The results of the research indicate that knowledge sharing and business process management play a mediating role in influencing the quality of information on the innovative performance of SMEs.Information quality has an impact on knowledge sharing, business process management and innovative performance of SMEs. Knowledge sharing and business process management affect the innovative performance of SMEs. SMEs should continuously improve the quality of company information, and by using this information, and through knowledge sharing and business process management, improve innovative performance.